Upaya Meningkatkan Motivasi Belajar Siswa Melalui Permainan Jala Ikan dalam Pembelajaran PJOK di SDN Betet 3 Kota Kediri - Yoga Pramudya Wardana; M. Akbar Husein Allsabah; Moh. Aan Zainul Arifin (JURNAL ILMIAH NUSANTARA, 2025)
This study used a cyclical Classroom Action Research (CAR) method to optimize student motivation in Physical Education, Sports, and Health (PJOK). Twenty-eight third-grade students from SDN Betet 3 participated as subjects. The study was divided into two cycles, each with planning, implementation, observation, and evaluation phases.The results showed that student learning motivation averaged 55.7% in Cycle I, then significantly increased to 73.56% in Cycle II. This 17.86% increase reflects a positive shift in student enthusiasm and interest in learning. The implementation of the "fishing net game" and refresher activities in Cycle II proved successful in increasing student learning motivation.The research findings demonstrate the effectiveness of a more interactive and engaging learning approach. The improvements implemented in Cycle II successfully created a more supportive learning environment. This study validates the effectiveness of the cyclical CARK method and the implementation of the "fishing net game" in increasing motivation in PJOK learning. The results emphasize the urgency of implementing innovative learning strategies to achieve maximum learning outcomes.